Biosynthesis of the C15-acetogenin laurepoxide may involve bromine-induced skeletal rearrangement of a Δ4-oxocene precursor. Issue 23 (3rd June 2015) - Taylor, Michael T.; Fox, Joseph M.
Graphical abstract: Abstract: An electrophilic bromine catalyzed skeletal rearrangement of an Δ4-oxocene to an epoxy furan has been described. This skeletal rearrangement suggests a plausible mechanism for the biosynthesis of the C15-acetogenin laurepoxide.